Boundary spanning leadership among community-engaged faculty: An exploratory study of faculty participating in higher education community engagement - Purcell, Jennifer W.; Pearl, Andrew; Van Schyndel, Trina (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2020)
The purpose of this study was to explore faculty members’ perceptions of their roles as boundary spanners, the expectations they have for professional competencies related to boundary spanning, and how these faculty were prepared to successfully perform in their boundary-spanning leadership roles. In the context of higher education community engagement, boundary spanning refers to the work that is critical in overcoming the divide between the institution and the community (Weerts & Sandmann, 2010). This study revealed boundary-spanning faculty leaders’ perceptions of their roles, competencies for effective community-engaged teaching and scholarship, and ways in which institutions may cultivate and support boundary-spanning leadership among current and future scholars and educators.